Critical thinking by nurses on ethical issues like the termination of pregnancies - Botes, A (Curationis (Pretoria), 2000)
This research forms part of a larger interdisciplinary research project on the termination of pregnancies. The focus of this part of the project is on the ethical issues related to termination of pregnancies. The practice of the professional nurse is confronted with ethical dilemmas and disputes. Whether the nurse chooses to participate in the termination of pregnancies or not, the core function of the nurse is that of counseling and ethical decision-making. Effective counseling requires empathy, respect for human rights and unconditional acceptance of a person. Making ethical decisions implies making critical decisions. It is self-evident, therefore, that such decisions should be based on sound arguments and logical reasoning. It is of vital importance that ethical decisions can be justified on rational ground. Decision-making is a critical thinking approach process for choosing the best action to meet a desired goal. The research question that is relevant for this paper is: Are nurses thinking critically about ethical issues like the termination of pregnancies? To answer the research question a qualitative, exploratory, descriptive design was used (Mouton, 1996:103-169). Registered nurses were selected purposively (Creswell, 1994:15). 1200 registered nurses completed the open-ended questionnaires. Focus group interviews were conducted with 22 registered nurses from a public hospital for women and child health services. Data analysis, using secondary data from open-ended questionnaires and transcribed focus group interviews, were based on the approach of Morse and Field (1994:25-34) and Strauss and Corbin (1990). The themes and categories from open coding were compared, conceptualized and linked with theories on critical thinking (Paul, 1994; Watson & Glaser, 1991 and the American Philosophical Association, 1990). The measures of Lincoln and Guba (1985) and Morse (1994) related to secondary data analysis were employed to ensure trustworthiness. Based on these findings the researcher concluded that nurses are not thinking critically when making ethical decisions concerning the termination of pregnancies. Recommendations are made as a possible solution for this problem.